Augmented Reality Enhanced NFT Arts to Raise Awareness of the Endangerment of Thai Tokay Geckos - Karnchanapayap, Gomesh (วารสารศิลปกรรมบูรพา, 2023)
Non-fungible tokens (NFTs) are a type of digital asset intended to indicate ownership of a unique item, such as an artwork or collectible. They are stored on a blockchain, which enables their secure and transparent purchase and sale. NFT art is not only a new medium for creative economics, but it can also be utilized creatively to draw attention to significant causes. The Thai tokay gecko is a gecko species indigenous to Thailand. Unfortunately, the Thai tokay gecko is threatened by habitat loss and degradation, as well as collection for the pet trade. In addition, the species is occasionally harvested for traditional medicinal purposes. The goals of this study were to: 1) analyze NFT as a new creative economy platform; 2) produce a collection of NFT arts based on the Thai tokay gecko to raise awareness about the species’ extinction; and 3) assess the effectiveness of the augmented reality-enhanced Thai tokay gecko NFT arts. To collect qualitative data, a total of 12 expert interviews were conducted. The expert interviews provided significant insights and a thorough overview of the Thai NFT art landscape. These data were utilized to create the Thai tokay gecko NFT collection, which included 30 artworks embedded with an augmented reality message concerning the species’ endangerment. 178 questionnaires were distributed online and inquired about respondents’ opinions on the NFT artworks.